Finite Automata and Application to Cryptography - Tao, Renji. (Springer Berlin Heidelberg, 2009)
Finite Automata and Application to Cryptography mainly deals with the invertibility theory of finite automata and its application to cryptography. In addition, autonomous finite automata and Latin arrays, which are relative to the canonical form for one-key cryptosystems based on finite automata, are also discussed. Finite automata are regarded as a natural model for ciphers. The Ra Rb transformation method is introduced to deal with the structure problem of such automata; then public key cryptosystems based on finite automata and a canonical form for one-key ciphers implementable by finite automata with bounded-error-propagation and without data expansion are proposed. The book may be used as a reference for computer science and mathematics majors, including seniors and graduate students. Renji Tao is a Professor at the Institute of Software, Chinese Academy of Sciences, Beijing.